SMALL AND MEDIUM ENTERPRISE PERCEPTION OF HALAL CERTIFICATION POST FORMALIZATION OF ISLAMIC CITY BRANDING - Arifin, Nur Rachmat; Muhtadi, Ridan; Herianingrum, Sri (UNISSULA, 2019)
SMEs (Small and Medium) are a solution to improve the economic sector and recorded in the Ministryof SMEs increasing from 57.84 percent to 60.34 percent by absorbing labor in the country, but the public and companies do not know much about Halal Certification in Bangkalan, Pamekasan, and Pasuruan, Madura Island that the majority of the people of Islam, past cultural and religious beliefs is still maintained so that its people follow traditional traditions, Madurese in all cities, one of them is Pasuruan, Pasuruan city as the main stopover city for Muslim traders from inside the country and abroad. This research aims to find out how to understand SMEs about halal certification which already has the Islamic City Branding, This research aims to know how to understand SMEs about halal certification that has had the slogan Islamic City Branding, This research uses a descriptive qualitative research method, with sampling techniques using snowball sampling. The primary data sources used in this study were documentation and direct interviews with SMEs in culinary fields in Bangkalan, Pamekasan, and Pasuruan Samples criteria in this study are the SMEs culinary fields in the 3 districts consist of 20 people each in each sub-district, while secondary data sources were obtained from books and journals. The results of this study indicate that as many as 39 or 65% of informants perceive that halal certificates are not important and only 21 or 35% of informants who consider halal certificates are important, Many challenges and problems faced in the development of halal lifestyle in Pasuruan and Madura, then the author gave a strategy that must be applied is thorough and answer all the challenges as existing problems, can increase core competencies of SMEs and ultimately increase competitiveness.